Pengaruh Arsitektur Tradisional Terhadap Desain Modern Dalam Upaya Melestarikan Identitas Budaya Lokal Indonesia - Putri Lanmindo Siregar, Dedek (Venustas, 2024)
Traditional Indonesian architecture embodies a rich blend of aesthetic, functional, and philosophical values that reflect local cultural identity. In the modern era, the sustainability of these values faces challenges due to globalization and urbanization, which tend to adopt universal architectural styles. This study aims to examine the influence of traditional architecture on modern design as an effort to preserve local cultural identity. The research methodology involves literature analysis, case studies of modern buildings that incorporate traditional elements, and interviews with local architects. The findings reveal that the application of traditional architectural elements, such as spatial patterns, local materials, and distinctive ornaments, can create modern designs that are not only aesthetically pleasing but also reinforce cultural values. Moreover, this integration supports environmental sustainability through the use of eco-friendly materials and traditional construction techniques adaptive to climatic conditions. The study concludes that the collaboration between tradition and innovation in modern design serves as an effective strategy for preserving Indonesia's local cultural identity amidst modernization.